Awareness and Use of Digital Reference Services in Academic Libraries in Ghana - Serwaa, Naomi Amofa; Dadzie, Perpetua S.; OWUSU-ANSAH, CHRISTOPHER (International Journal of Knowledge Content Development & Technology, 2022)
The traditional reference service in academic libraries is gradually integrating digital modes of communication culminating in digital reference services (digital reference services). This study seeks to explore the extent to which digital reference services support user needs in academic libraries in Ghana. Specifically, the study was concerned with users’ awareness, preference and motivation for using digital reference services in three selected Academic Libraries in Ghana. Making use of a mixed-method research design, a total of 413 digital reference services users, 3 heads of university libraries, 3 heads of Information Technology (IT) and 7 digital reference services Librarians, from across three Academic Libraries, were selected to participate in the study. The results indicated that despite the utility of both, there was a preference for traditional reference in the three Academic Libraries. However, the use of digital reference services surged during quizzes, mid-semester examinations, interim assessments and end-of-semester examinations. With respect to the popularity of the various digital reference services platforms, users preferred email over other digital platforms. The results also indicated that the respondents used digital reference services when they were off-campus, while mobile phones were the most common digital tool for accessing digital reference services. Ultimately, digital reference services were found to considerably improve the use of library services. Implications of the results are discussed.